2012
DOI: 10.1111/j.1365-2265.2011.04314.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid replacement therapy and fibrinolysis in patients with hypopituitarism

Abstract: An increased dose of hydrocortisone for 2 weeks creates excessive glucocorticoid exposure, but does not significantly affect fibrinolytic-coagulation parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Peacey et al (115) found that an increased dose of HCT for 2 weeks did not significantly affect PAI1, tPA or FBR levels in patients with hypopituitarism.…”
Section: Secondary Aimentioning
confidence: 99%
“…Peacey et al (115) found that an increased dose of HCT for 2 weeks did not significantly affect PAI1, tPA or FBR levels in patients with hypopituitarism.…”
Section: Secondary Aimentioning
confidence: 99%
“…[ 39 ] Furthermore, glucocorticoid (GC) over-replacement and a lack of sex steroids contribute to impaired metabolic parameters and atherogenesis in patients with hypopituitarism. [ 40 41 ]…”
Section: Discussionmentioning
confidence: 99%